Performance blocks in sport: Recommendations for treatment and implications for sport psychology practitioners. Issue 1 (2nd January 2017) - Bennett, Jenn; Maynard, Ian
ABSTRACT: Sport psychologists are increasingly confronted with performance difficulties where athletes mysteriously lose the ability to execute automatic movements. Traditionally referred to as the yips or lost move syndrome, the generic term performance blocks has recently been put forward to encompass these types of problems that manifest in locked, stuck, and frozen movements, loss of fine and/or gross motor control, and debilitating anxiety. Two recent investigations examined the effectiveness of eye movement desensitization and reprocessing with graded exposure to treat two performance block-affected individuals. Evaluation of the interventions showed improved performance of the affected skills and reduced anxiety in both cases. Interview data collected on completion of each intervention confirmed that associated symptoms were also alleviated. The success of these two interventions offers considerable value to sport psychologists, the implications of which the current article hopes to address. Specifically, the manuscript provides an overview of current research pertaining to performance blocks, followed by recommendations for treatment and implications for sport psychologists. The importance of involving clinical psychology support in formulation and treatment processes of performance blocks is highlighted, and a call for further research investigating treatment is put forward.